EFL idiom instruction: Teacher practices and challenges - Mohamed Amin Mekheimer (Social Sciences and Humanities Open)
This study addresses the critical gap in EFL idiom instruction research concerning teachers' experiences and challenges, focusing specifically on the study context. Existing research predominantly evaluates teaching methods without adequately addressing practical classroom realities. This mixed-methods study, involving 300 teacher questionnaires (including both quantitative Likert scale and qualitative open-ended questions), 18 semi-structured interviews, and 18 focus groups, investigated (1) prevalent idiom teaching strategies among EFL teachers; (2) the major challenges they face; and (3) the relationship between these strategies and challenges. Results revealed that while teachers creatively employ contextualized and culturally sensitive approaches, they encounter significant resource limitations, inadequate curriculum support, and difficulties in assessing student understanding beyond rote memorization (reported by approximately 35 % of participants). Quantitative analysis of the survey data confirmed a strong preference for authentic materials and engaging activities, significantly correlating with reduced perceived challenges. Qualitative analysis of both open-ended survey responses (n = 300) and interview/focus group data (n = 18) highlighted key themes of resource scarcity, cultural barriers, curriculum constraints, and the need for collaborative professional development. These findings underscore the urgent need for targeted interventions—including the development of culturally appropriate resources, enhanced teacher training programs focused on communicative assessment, and supportive institutional policies—to significantly improve idiom instruction and enhance EFL learners’ communicative competence in EFL contexts.